Estudo de concretos com pozolanas submetidos à carbonatação em ensaios acelerado e natural monitorado por 20 anos - Silveira, Rodrigo Goettems da (2019)
Carbonation, a potentially aggressive chemical reaction to concrete, is a slow process and difficult to detect in the short term through accelerated testing. In this work were studied concretes with fly ash (CV) and rice husk ash (CCA) replacing 25% Portland cement in binary mixtures and 10% CV + 15% CCA in ternary mixtures submitted to indoor carbonation for 20 years and compared with reconstituted concretes under accelerated carbonation with 3% CO2 for 20 weeks. The microstructural and chemical analyzes showed, in most of the mixtures, similarities between the two tests, both in carbonate depth and in the influence of carbonation on porosity, through the redistribution of pore diameters, and in the chemical composition of concretes by the decomposition of portlandite in carbonated layer (CS) of material. It was found that carbonation consumed the entire Portlandite of CS from pozzolan concretes under natural process and the binary mixtures submitted to the accelerated process. Porosimetry tests showed that, with the exception of ternary mixtures, carbonation reduced the total pore volume of concretes. The data collected from the two test modalities were used to develop an easy-to-perform calculation method to predict the long-term carbonated depth of the concrete and to determine the carbonation coefficient of the material. It was observed that the addition of pozzolans to the concrete in the tested contents is feasible for a water / cementitious materials ratio of 0.45 in the studied period without great prejudice regarding the material performance against carbonation.